Glassy dynamics of a polymer monolayer on a heterogeneous disordered substrate. Issue 41 (4th September 2015) - Pastore, Raffaele; Raos, Guido
Abstract : The dynamics of polymers adsorbed on heterogeneous solid substrates becomes surprisingly sluggish on cooling. Abstract : We present molecular dynamics simulations of a polymer monolayer on randomly functionalized surfaces that are characterized by different fractions of weakly and strongly attractive sites. We show that the dynamics slow-down upon cooling resembles that of a strong glass-forming liquid. Indeed, the mean-square displacements show an increasingly lasting subdiffusive behaviour before the diffusive regime, with signs of Fickian yet not Gaussian diffusion, and the dynamic correlation functions exhibit a stretched exponential decay. The glassy dynamics of this relatively dilute system is dominated by the interaction of the polymer with the substrate and becomes more marked when the substrate composition is heterogeneous. Accordingly, the estimated glass transition temperature shows a non-monotic dependence on surface composition, in agreement with previous results for the activation energy and with an analysis of the potential energy landscape experienced by the polymer beads. Our findings are relevant to the description of polymer–surface adhesion and friction and the development of polymer nanocomposites with tailored structural and mechanical properties.